DISTINCTIVE CHARACTERISTICS OF DIALECTAL PHRASEOLOGISMS AND THEIR PLACE IN LINGUISTIC STUDIES (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article scientifically substantiates the distinctive features of dialectal phraseologisms and their role in Uzbek linguistics. It explores the close connection between dialectal phraseological units and the people's lifestyle, culture, beliefs, and occupational activities. The phonetic, lexical, and semantic characteristics of these expressions are examined, along with their differences and similarities with those in the literary language.